The complete chloroplast genome of Syzygium acuminatissimum. Issue 1 (2nd January 2021) - Zeng, Feng; Deng, Yanwen; Liu, Xiaozhou; Zhu, Xuanxi; Tan, Guangwen
Abstract: Syzygium acuminatissimum is a valuable hard wood species in southern China. In this study, we sequenced, assembled and annotated the complete chloroplast genome of S. acuminatissimum . The complete cp genome of S. acuminatissimum was 159, 352 bp in length, with a total of 109 unique annotated genes, including 78 protein-coding genes, 27 tRNA genes and 4 rRNA genes. Phylogenetic analysis showed that S. acuminatissimum was closely related to its congener S. aromaticum .